2018
DOI: 10.3389/fpsyg.2018.02118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Musical Tempo on Musicians’ and Non-musicians’ Emotional Experience When Listening to Music

Abstract: Tempo is an important musical element that affects human’s emotional processes when listening to music. However, it remains unclear how tempo and training affect individuals’ emotional experience of music. To explore the neural underpinnings of the effects of tempo on music-evoked emotion, music with fast, medium, and slow tempi were collected to compare differences in emotional responses using functional magnetic resonance imaging (fMRI) of neural activity between musicians and non-musicians. Behaviorally, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 86 publications
2
41
0
2
Order By: Relevance
“…1 in G Major”; n = 67), or no music ( n = 64). These three musical pieces were chosen specifically due to their similar tempos (ranging from 120 to 185 beats per minute, all falling within the allegro or presto range, both considered to be moderately fast; Liu et al., 2018), and because the lyrics of both the Christian hymn (sung by an Anglican Choir) and the Buddhist chant were generally unintelligible, so not to interfere with reading comprehension or memory performance (Alley & Greene, 2008; Thompson et al., 2012), or to sound notably different from the instrumental classical piece.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 in G Major”; n = 67), or no music ( n = 64). These three musical pieces were chosen specifically due to their similar tempos (ranging from 120 to 185 beats per minute, all falling within the allegro or presto range, both considered to be moderately fast; Liu et al., 2018), and because the lyrics of both the Christian hymn (sung by an Anglican Choir) and the Buddhist chant were generally unintelligible, so not to interfere with reading comprehension or memory performance (Alley & Greene, 2008; Thompson et al., 2012), or to sound notably different from the instrumental classical piece.…”
Section: Methodsmentioning
confidence: 99%
“…First, responses were only collected from Christians and Atheists, and related to only to a limited selection of religious (Christian hymns, Buddhist chants) and non‐religious (classical) music. Future research might consider including music and participants from a greater diversity of genres and religions, as well as a broader range of tempos (Liu et al., 2018). In addition, although the patterns emerging as a function of (ir)religious group and music type appeared to be consistent, the effect sizes were relatively small.…”
Section: Caveats and Conclusionmentioning
confidence: 99%
“…With respect to the underlying mechanisms for this phenomenon, it was proposed that stimulating and motivational music impacts the brainstem reflex to stimulate the central nervous system toward heightened physiological arousal associated with high-intensity activity (Juslin, 2013; Terry et al., 2020). Liu et al. (2018) examined brain activation in response to music at different tempos, using functional magnetic resonance imaging (fMRI) and found that listening to fast-tempo music induced a stronger activation in the superior temporal gyrus bilaterally, providing neural evidence of affective valence with fast versus slow music.…”
Section: Discussionmentioning
confidence: 99%
“…Tempo is the pace or speed at which the music is played. A fast-paced rhythm and fast tempo can be more activating (higher arousal) than a slower paced rhythm (Iakovides, 2004;Hunter, 2010;Liu, 2018).…”
Section: Sonic Atmospherementioning
confidence: 99%